2020
DOI: 10.1175/jcli-d-19-0294.1
|View full text |Cite
|
Sign up to set email alerts
|

The Modulation of Gulf Stream Influence on the Troposphere by the Eddy-Driven Jet

Abstract: This study suggests that the Gulf Stream influence on the wintertime North Atlantic troposphere is most pronounced when the eddy-driven jet (EDJ) is farthest south and better collocated with the Gulf Stream. Using the reanalysis dataset NCEP-CFSR for December–February 1979–2009, the daily EDJ latitude is separated into three regimes (northern, central, and southern). It is found that the average trajectory of atmospheric fronts covaries with EDJ latitude. In the southern EDJ regime (~19% of the time), the freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…However, we note that the SST changes in other basins are minor compared to the North Atlantic and the GS in particular (see Figure ). We also note that similar basin wide changes associated with the GS shifts have previously been found in both observed air‐sea fluxes (Joyce et al., 2009; Parfitt & Kwon, 2020, relative to the overlying jet) and atmosphere only model experiments of mid‐latitude Atlantic storms (Lee et al., 2018).…”
Section: Resultssupporting
confidence: 84%
“…However, we note that the SST changes in other basins are minor compared to the North Atlantic and the GS in particular (see Figure ). We also note that similar basin wide changes associated with the GS shifts have previously been found in both observed air‐sea fluxes (Joyce et al., 2009; Parfitt & Kwon, 2020, relative to the overlying jet) and atmosphere only model experiments of mid‐latitude Atlantic storms (Lee et al., 2018).…”
Section: Resultssupporting
confidence: 84%
“…Furthermore, Rudeva et al (2019) also highlighted to first order that significant correlations exist between the number of fronts in the low midlatitudes and the location and intensity of the subtropical ridge, and an equatorward‐shifted southern hemisphere wintertime subtropical jet has also been shown to be eddy driven and associated with the poleward displacement of the eddy‐driven jet (Gillett et al, 2021). In addition, Parfitt and Kwon (2020) demonstrated that the trajectory of atmospheric fronts covaries with the latitude of the eddy‐driven jet.…”
Section: Resultsmentioning
confidence: 99%
“…[39]), but errors in wind speed and SST inputs are also important [41]. Several recent studies have indicated that spatial gradients in heat fluxes are of primary importance in determining the influence of western boundary currents such as the Gulf Stream, not just on the local atmospheric frontal variability, but also on the basin-wide circulation and time-mean atmosphere [10,46]. The effect of spatial resolution on these heat flux gradients can be seen in Figure 4e,f, which shows the time-mean spatial gradients for latent and sensible heat fluxes estimated from the WRF output decimated to 0.5 • resolution (current measurement capability corresponds to about 0.5 • resolution).…”
Section: Current Status Of Flux Estimatesmentioning
confidence: 99%
“…For example, atmospheric fronts cause up to 90% of the precipitation in mid-latitudes [76]. They also set the time-mean wind convergence and vertical motion throughout the troposphere [46,77], critical for hemispheric circulation [78]. In other words, through atmospheric fronts, WBCs can potentially modulate the atmosphere on all timescales.…”
Section: Implications For New Sciencementioning
confidence: 99%